PERANCANGAN APLIKASI PEMESANAN JASA FOTOGRAFI DAN VIDEOGRAFI PADA PERUSAHAAN UNIX PRODUCTION BERBASIS WEB - Ananta, Pramudya; Jimmie; Perdana, Meilyana Winda (Kohesi: Jurnal Sains dan Teknologi, 2024)
Unix production is a production house or PH that operates in the digital visual sector located in Palembang. Unix Production itself was only founded in 2021. The problem that occurs with the Unix Production company is that there is no company profile website and service orders, order data collection is still manual which causes difficulties for its employees. The research method used is a qualitative research method. The objectives of qualitative research are generally directed by the paradigm used by researchers in the study in each case. Quantitative research methods are methods for testing certain theories by looking at the relationships between variables. Variables are measured so that data is found in the form of numbers, which are then analyzed using statistical formulas. The aim is to control variance, and present answers to research questions through hypotheses. This hypothesis will be proven empirically through data collected in the field. This research produces a website-based application for ordering photography and videography services at Unix Production companies which can make it easier for Unix employees to collect data on service orders. From the research and implementation that has been carried out by the author in "Designing Applications for Ordering Photography and Videography Services at Unix Production Companies Based on Websites" can be concluded, namely increasing efficiency and effectiveness for employees who manage inputting order data at UNIX Production Companies. With this application, service orders can be quickly and easily responded to by UNIX Production staff.